Assessment of quality of life three years from hematopoietic stem cell transplant - Angela da Costa Barcellos Marques; Celina Angélica Mattos Machado; Dabna Hellen Tomim; Paulo Ricardo Bittencourt Guimarães; Jorge Vinicius Cestari Felix; Luciana Puchalski Kalinke (SciELO, 2021)
ABSTRACT Objective: To assess the domains of quality of life related to hematologic cancer patient health in the first three years from autologous and allogeneic hematopoietic stem cell transplantation. Method: A prospective cohort from September 2013 to February 2019 at a reference service in Latin America with 55 patients. The instruments Quality of Life Questionnaire Core C30 and Functional Assessment Cancer Therapy - Bone Marrow Transplantation were used. For data analysis, Generalized Linear Mixed Model was used. Results: The domains global and overall quality of life presented the lowest scores in the pancytopenia phase: 59.3 and 91.4 in autologous, 55.3 and 90.3 in allogeneic. The mixed method analysis has shown that there was a significant change in scores between the phases throughout the treatment (p< 0.05). Conclusion: Health-related quality of life presented significant changes in the domains between the phases throughout time. Understanding these results enables nursing interventions directed at the domains which were damaged during treatment.